Analyzing delays in trajectories - Konzack, Maximilian; McKetterick, Thomas; Wilcox, Georgina; Buchin, Maike; Giuggioli, Luca; Gudmundsson, Joachim; Westenberg, Michel A.; Buchin, Kevin (IEEE Pacific Visualization Symposium, 2015)
Interactions between trajectories need to be analyzed in various domains to gain insight into movement patterns. Such interactions often take place with some delayed response. We propose an approach to analyze and visualize delayed responses on two trajectories recorded simultaneously and with the same sampling rate. Central to our approach is the computation of a matching between the trajectories in a so-called delay space. We also introduce a new similarity measure between trajectories, which combines directional and spatial characteristics. To evaluate our approach experimentally, we have implemented it as a prototype visual analytics tool and have applied the tool on two datasets.